Collaborating Smartly: The Role of Open Strategy in Absorptive Capacity. (1st October 2019) - Pittz, Thomas G.; Intindola, Melissa L.; Adler, Terry; Rogers, Sean; Gard, Charlotte
Abstract : Research on open strategy suggests that shared knowledge through collaboration can generate co‐created value. We explore this idea by assessing it as a predictor of absorptive capacity (ACAP) in cross‐sector partnerships in pursuit of social innovation. The findings of our study indicate that aspects of strategic openness, including a shared sense of interdependence toward a mutual goal, are the primary mechanisms that enhance knowledge accretion in cross‐sector partnerships. The data also suggest that formalized organizational mechanisms are more influential for producing ACAP than informal mechanisms.